Tinjauan Etis-Teologis Terhadap Tradisi Belis Di Pulau Sumba Berdasarkan Konsep Mahar Dalam Alkitab: Ethical And Theological Analysis To The Belis Tradition In Sumba Based On Biblical Concept Of Dowry - Kamuri, Johanis Putratama; Toumeluk, Grace Mariany (Reformed Center for Religion and Society, 2021)
This paper is aimed to determine the appropriate Christian attitude towards the practice of belis (dowry) in Sumba Island. The biblical, anthropological, and sociological concepts of dowry are the conceptual framework for understanding and analyzing the concept of belis. Based on systematic reviews and asymmetric comparisons of the Sumbanese belis concepts and biblical concept of dowry, it is found that rejection of the practice of belis is unnecessary. Belis can be practiced by Sumbanese Christians with a critical attitude. The goal is the transformation of the belis culture. Transformation is achieved through several actions: doing belis principles that do not conflict with biblical principles; rejecting the principles that conflict with biblical principles; and avoiding the practices of belis which have been distorted by deviating motivations either from the biblical or the rights belis principles. Keywords: Belis; Dowry; Marapu; Sumba; Cultural Transformation.